Challenges in Attaining Sustainable Development Goals in Port Klang: Port Management Perspective - Prashanth Beleya; Geetha Veerappan; Wong Jian Ding; Jason Tan (International Journal of Supply Chain Management, 2020)
Sustainable development goals revolve around three broad elements: cost reduction, productivity enhancement and environmental protection. Seaport industry is inextricably linked to enormous competitions; requiring unceasing improvements to be able to achieve competitive advantages by addressing the relevant sustainable development goals. Dynamic capabilities theory is incorporated in this study to substantiate the relationship between sustainable development goals and sustainable competitive advantages. In addition, dynamic capabilities theory provides a guideline for port management in ascertaining efforts needed to stay relevant in the ever demanding seaport business. Nonetheless, in the process of attaining sustainable development goals, challenges are faced by port management. This study incorporates a qualitative approach, focusing in port Klang particularly on Northport and Westport due to the high volume of cargo handled and being national economic barometers. Interviews were conducted whereby the respondents were managerial personnel in their respective departments. The findings indicate that the challenges in attaining sustainable development goals comprise of technological constraints, financing issues, human capital barriers and supplier associated problems. Addressing these stumbling blocks proves advantageous for port Klang whereby the attainable sustainable development goals is a catapulting factor for ports to achieve sustained competitive advantages in the future.